2014
DOI: 10.5114/hpr.2013.40467
|View full text |Cite
|
Sign up to set email alerts
|

Resiliency and the subjective evaluation of health in mothers of children with Asperger’s syndrome

Abstract: <b>Background</b><br /> Parents caring for children with developmental disorders are exposed to much higher levels of stress than parents of typically developing children. It has also been proved that parents of children with developmental disorders experience mental health deterioration, a sense of guilt, physical weakness, fatigue and exhaustion. Resiliency conditions cognitive and emotional flexibility, and enables an individual to adjust their own behavior to particular circumstances. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Therefore there is a differentiation between resilience and resiliency. Many authors, including the creators of the notion (Block & Block, 1980;Uchnast, 1997;Letzring, Block, & Funder, 2005;Kasprzak, Basińska, & Lewandowska, 2013), treat resiliency as a relatively permanent disposition of an individual. It is also acknowledged to be a resource which appears most often via experiencing serious difficulties and threats under which a person displays signs of positive adaptation (Ogińska-Bulik & Juczyński, 2008a, 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore there is a differentiation between resilience and resiliency. Many authors, including the creators of the notion (Block & Block, 1980;Uchnast, 1997;Letzring, Block, & Funder, 2005;Kasprzak, Basińska, & Lewandowska, 2013), treat resiliency as a relatively permanent disposition of an individual. It is also acknowledged to be a resource which appears most often via experiencing serious difficulties and threats under which a person displays signs of positive adaptation (Ogińska-Bulik & Juczyński, 2008a, 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the importance of psychological resiliency for the functioning of people in different situations, especially those experiencing negative life events (Felcyn-Koczewska & Ogińska-Bulik, 2011;Ogińska-Bulik, 2010, 2013Ogińska-Bulik & Juczyński, 2012). It was also shown that resiliency plays the role of a protective factor against the negative effects of experienced occupational stress (Ogińska-Bulik, 2011a), conducive to adaptation to the disease (Ogińska-Bulik & Juczyński, 2012; Kasprzak, Basińska, & Lewandowska, 2013;Ogińska-Bulik, 2011b;Sęk, Kaczmarek, Ziarko, Pietrzykowska, & Lewicka, 2012;White, Driver, & Warren, 2010) and supporting adaptive functioning in difficult life situations (Grzankowska, Napora, & Basińska, in print). The dynamism can be developed and shaped by strong motivation and willingness to learn and a flexible approach to life experiences.…”
Section: Psychological Resiliencymentioning
confidence: 99%
“…Zmęczenie przewlekłe jest problemem dotyczącym coraz większej liczby osób. Na zwiększenie częstotliwości odczuwanych objawów zmęczenia przewlekłego w dzisiejszych czasach bezsprzecznie wpływają rodzaj wykonywanej pracy [7], tempo życia oraz wymagania środowiskowe [8] i życiowe [9,10].…”
Section: Zmęczenie Przewlekłeunclassified